Conformability of Five Brands of Vegetable Oil Sold in Roban Stores Awka, Nigeria to NAFDAC Set Standards (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
The study investigated the conformability of five brands of vegetable oil sold in Roban stores Awka to NAFDAC set standards. The oil brands used were; Sunchi soya oil (CBI), Carlini pure canola oil (ABI), Lassa vegetable oil (NEI), Golden penny pure soya oil (NMN), and Activa pure vegetable oil (JGO). The result obtained for the physical properties of the oils differed significantly (p ≤ 0.05) and ranged from 0.65-0.92, 1.33-1.54 and 50.55-80.44 mPa・s for specific gravity, refractive index, and viscosity respectively and were below the standard set by NAFDAC for oils (0.91-0.92, 1.46-1.48) except for sample CBI with a specific gravity of 0.92 and refractive index of 1.46. However, all oil samples analyzed met the standard of ≥ 0.2 set by NAFDAC for viscosity. Furthermore, the values obtained for Saponification number, Iodine value, and Peroxide value differed significantly (p ≤ 0.05) and ranged between 145-190 mg KOH/g, 0.90-8.86 mgI2/g and 1.70-7.48 meq/kg respectively. They complied with NAFDAC standards (190-209 mg KOH/g, 50-55 (Wijs) and ≤ 10 meq/kg). Other chemical properties analyzed were Free fatty acid, pH, Base value and impurity level. The standards of these parameters were not set by NAFDAC. Their values ranged from 3.40-6.31 mg/g KOH, 8.4-12, 8.4-12, and 0.13-0.60 respectively. The values of all parameters analyzed were within the NAFDAC recommended standard for edible oil. Thus, indicating that the oil samples studied were of good quality and suitable for consumption.
Keywords: FFA; Peroxide values; Saponification value; Specific gravity; Vegetable oil